Incident angle model of measuring light in gear measurement utilizing a line laser sensor and analysis on its influence factors. (15th November 2022) - Sun, Yanqiang; Shi, Zhaoyao; Yu, Bo; Li, Haobin
Highlights: The mathematical model of incident angle is defined, established, and verified. The influence factors of the incident angle is explored. Good suggestions are given to reduce the impact of incident angle on measurement accuracy. Abstract: Fast acquisition of the integral tooth surface data is significant in the quality evaluation of gears. The line laser measurement provides an efficient solution to acquire the above data, but its measurement accuracy remains to be improved. A too large incident angle of measuring light seriously affects the integrity of the obtained tooth surface data, thus limiting the extraction of effective tooth surface and the quality evaluation of tooth surface. In order to clarify the influences of incident angle of measuring light on the acquired tooth surface data in the gear measurement, taking a cylindrical gear as an example, a mathematical model of incident angle is established. It is verified by simulation analysis and five groups of measuring experiments. Based on the simulation results and experimental data, the influences of offset and inclination angle of the laser sensor on the incident angle of measuring light are further analyzed. The incident angle decreases significantly with the increase in the offset. The influence of the inclination angle smaller than 60° on the incident angle is insignificant and could be ignored. In addition, according to the types of gears, the reasonable position and attitude of the sensor are determined to reduce the influence of the incident angle of measuring light on measurement accuracy.